CURRICULUM MANAGEMENT OF JUNIOR HIGH SCHOOL BASED ON BOARDING SCHOOL AT SYUHRATUL ISLAM GELUMBANG JUNIOR HIGH SCHOOL - Muhthadi, Muhthadi; Fauzi, Muhammad; Imron, Kristina; Dahari, Dahari (Jurnal Asy-Syukriyyah, 2025)
This study examines the implementation of the management of the Islamic boarding school-based junior high school curriculum at Syuhratul Islam Gelumbang Junior High School with a descriptive qualitative approach. The focus of the study is on four management functions: planning, organizing, implementing, and evaluating an integrated curriculum that integrates the national curriculum (K13) with the Islamic boarding school curriculum. The results of the study indicate that curriculum planning is carried out collaboratively involving all stakeholders based on the vision of producing a globally competitive Quranic generation. The organization of the curriculum applies the principle of maintaining a good traditional system while adopting relevant innovations. The implementation of the curriculum is implemented through a variety of learning methods that are adjusted to the characteristics of the subjects. Evaluation is carried out in stages and continuously covering aspects of attitude, knowledge, and skills. The integrated curriculum model with three main pillars of Adab, Al-Qur'an, and Diniyah has proven to be successful in improving the quality and quantity of graduates, making a significant contribution to the development of a modern Islamic boarding school education model